LEMBAGA PENDIDIKAN SEKOLAH DAN MADRASAH (PEMBAHARUAN METODE DAN SISTEM PENDIDIKAN) - Husyin Saputra; Bahaking Rama; Muhammad Rusydi Rasyid (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This study aims to find out the renewal of education methods and systems. The ultimate goal of Islamic education is to form pious human beings so that they are safe in their lives. The renewal of the Islamic education system is something that is carried out effectively, efficiently and productively towards progress. The renewal in question is renewal in education, namely a change that is new and deliberately attempted to achieve certain goals in education. Educational renewal includes 4 aspects namely; renewal in the aspect of educational goals, renewal in the curriculum aspect, reform in the educator aspect, and renewal in the student aspect